2023
DOI: 10.1021/acsnano.2c07970
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Expression of De Novo Designed Peptides That Form β-Barrel Nanopores

Abstract: Nanopore sensing has attracted much attention as a rapid, simple, and label-free single-molecule detection technology. To apply nanopore sensing to extensive targets including polypeptides, nanopores are required to have a size and structure suitable for the target. We recently designed a de novo β-barrel peptide nanopore (SVG28) that constructs a stable and monodispersely sized nanopore. To develop the sizes and functionality of peptide nanopores, systematic exploration is required. Here we attempt to use a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In addition, SVG28 detects cationic peptides more efficiently than the commonly used αHL nanopore due to its terminal charge. Moreover, Fujita et al have found that a hydrophilic variant of SVG28 can be synthesized using CFPS, which retained the pore-forming ability 123 ( Fig. 5(e) ), promising easy access to peptide nanopores for molecular robotics.…”
Section: Sensors Of Molecular Robotsmentioning
confidence: 99%
“…In addition, SVG28 detects cationic peptides more efficiently than the commonly used αHL nanopore due to its terminal charge. Moreover, Fujita et al have found that a hydrophilic variant of SVG28 can be synthesized using CFPS, which retained the pore-forming ability 123 ( Fig. 5(e) ), promising easy access to peptide nanopores for molecular robotics.…”
Section: Sensors Of Molecular Robotsmentioning
confidence: 99%
“…17 Moreover, we further showed that these peptides can be formed by cell-free synthesis after introducing hydrophilic substitutions. 18 While the β-hairpin has been shown useful for nanopore sensing, the construction of de novo α-helical nanopores capable of transporting biomolecules is still of great interest and has never been realized to date.…”
Section: •Mainmentioning
confidence: 99%
“…These cell-free systems are flexible, enabling the adjustment of the environmental conditions for (i) functionally expressing difficult enzymes ( e.g. , membrane proteins, oxygen-labile proteins, and antibodies), toxic proteins, noncanonical peptides, , and nonribosomal peptide antibiotics with high homogeneity and (ii) screening metagenome-derived functional proteins, active protein mutants in protein evolution, and de novo designed polypeptides. , Furthermore, cell-free systems enable protein expression from linear DNA, bypassing the procedures of plasmid cloning and microbe culturing, which often cause sequence mutations. However, unlike cellular life, which couples the central dogma to metabolism-expressing biosynthetic enzymes to regenerate the cellular building blocks via enzyme-driven metabolism, any artificial life designed with cell-free systems as the components of biological information transfer entirely relies on an external supply of protein synthesis building blocks ( i.e ., AAs) rather than any coupled metabolic mechanism.…”
Section: Introductionmentioning
confidence: 99%